Electronic, Structural and Functional Versatility in Tetrathiafulvalene‐Lanthanide Metal–Organic Frameworks. Issue 54 (5th September 2019) - Castells‐Gil, Javier; Mañas‐Valero, Samuel; Vitórica‐Yrezábal, Iñigo J.; Ananias, Duarte; Rocha, João; Santiago, Raul; Bromley, Stefan T.; Baldoví, José J.; Coronado, Eugenio; Souto, Manuel; Mínguez Espallargas, Guillermo
Abstract: Tetrathiafulvalene‐lanthanide (TTF‐Ln) metal–organic frameworks (MOFs) are an interesting class of multifunctional materials in which porosity can be combined with electronic properties such as electrical conductivity, redox activity, luminescence and magnetism. Herein a new family of isostructural TTF‐Ln MOFs is reported, denoted as MUV‐5(Ln) (Ln=Gd, Tb, Dy, Ho, Er), exhibiting semiconducting properties as a consequence of the short intermolecular S⋅⋅⋅S contacts established along the chain direction between partially oxidised TTF moieties. In addition, this family shows photoluminescence properties and single‐molecule magnetic behaviour, finding near‐infrared (NIR) photoluminescence in the Yb/Er derivative and slow relaxation of the magnetisation in the Dy and Er derivatives. As such properties are dependent on the electronic structure of the lanthanide ion, the immense structural, electronic and functional versatility of this class of materials is emphasised. Abstract : Hot MOFs : Herein a new family of isostructural TTF‐Ln MOFs (Ln=Gd, Tb, Dy, Ho, Er), named MUV‐5, are presented, exhibiting electrical conductivity, NIR luminescence and magnetic properties.